PROPOSAL FOR A TEACHING METHODOLOGY FOR THE ADAPTATION OF DESCRIPTIVE GEOGRAPHY SUBJECTS TO THE EHEA: THE CASE OF THE GEOGRAPHY OF EUROPE - ÁNGEL LUIS LUCENDO MONEDERO (Didáctica Geográfica)
The objective of this communication is to present the most significant aspects of the teaching experience carried out in the Geography of Europe of the first year in Geography and Territory Management degree in the Seville University during the year 2014/2015. The experiment consisted in designing, implementing and evaluating a new methodology for the teaching and learning of active character, autonomous and based on problems (in English New Education in Works, paraphrasing, New Method based on jobs). The NEW methodology is opposed and replaces Traditional Teaching Methods (MDT) that is commonly used in the teaching of the subjects of Geography of descriptive type or general.